Effect of Mother-Baby Friendly Facility Accreditation on Midwifery Staff’s Perceptions of Obstetric Mistreatment - Tercan, Can; Yeniocak, Ali Selcuk; Dagdeviren, Emrah; Akay, Emrullah (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objective(s): This study aimed to evaluate the impact of Mother-Baby Friendly Facility (MBFBF) accreditation on midwifery staff's perceptions of obstetric mistreatment. The hypothesis tested was that MBFBF-associated training and policy changes would improve awareness and reduce tolerance toward mistreatment practices during childbirth. Study Design: This single-center observational pre-post study was conducted in the obstetrics and gynecology unit of a tertiary hospital. Data collection occurred before and after MBFBF accreditation, granted in November 2024. The study included 122 midwifery staff with at least one years of clinical experience before accreditation. Perceptions of obstetric mistreatment were assessed using the Turkish version of the Perception of Obstetric Violence in Students Questionnaire (PercOV-S Q). Statistical analyses included Wilcoxon signed-rank, Mann-Whitney U, and Kruskal-Wallis tests to evaluate changes in scores and subgroup differences. Results: Significant improvements were observed in perceptions of mistreatment, with overall PercOV-S Q scores increasing from 95.50 (87.00–107.00) pre-intervention to 110.50 (83.50–129.00) post-intervention (p = 0.027). Key areas of improvement included informed consent (Q1: p < 0.001), privacy (Q2: p < 0.001), and respectful communication (Q3: p = 0.017). Subgroup analysis showed statistically significant differences in five selected questions (p < 0.001), while other areas showed trends toward improvement. Conclusion(s): The MBFBF accreditation process and associated training significantly enhanced midwifery staff's awareness of obstetric mistreatment, aligning with international guidelines. These findings underscore the importance of structured education and institutional reform in fostering respectful, patient-centered care. Expanding MBFBF accreditation programs globally could contribute to reducing obstetric mistreatment and improving maternal health outcomes.